2009
DOI: 10.1007/s11666-009-9363-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of CFD Modeling via Flow Visualization in Cold Spray Process

Abstract: The two-phase flow properties of copper particle laden nitrogen are computationally modeled and compared with the data obtained from the experiments, determining the achievable degree of consistency between model and reality. Two common, commercial nozzles are studied. A two-way coupled Lagrangian scheme along with the RSM turbulence model is used to track the particles and to model the interactions between the gas and the particulate phase. Significant agreement is found for the geometrical gas flow structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 13 publications
1
26
0
Order By: Relevance
“…Nevertheless, depending on the particle feed rate and the relative gas consumption, the discrete phase loading can increasingly affect the acceleration process at higher feed rate levels. Results demonstrated by Samareh et al [22] indicated that the gas flow structures change and the particle speed reduces as their mass fraction increases. Accordingly, a study by Lupoi [23] showed that a number of experimental observations with various nozzle geometries could not be explained by 1-way coupling CFD techniques.…”
Section: Introductionmentioning
confidence: 97%
“…Nevertheless, depending on the particle feed rate and the relative gas consumption, the discrete phase loading can increasingly affect the acceleration process at higher feed rate levels. Results demonstrated by Samareh et al [22] indicated that the gas flow structures change and the particle speed reduces as their mass fraction increases. Accordingly, a study by Lupoi [23] showed that a number of experimental observations with various nozzle geometries could not be explained by 1-way coupling CFD techniques.…”
Section: Introductionmentioning
confidence: 97%
“…This makes further development of more advanced methods and their validation necessary. It could be suggested to make use of a Reynolds-stress model (RSM) that was successfully applied in CS applications in good agreement with experimental observations (Samareh et al, 2009).…”
Section: Coupled Simulationmentioning
confidence: 76%
“…A limit of this type of model is the dependency of its validity on relatively high particle density and uniform distribution. The same authors contributed with another publication (Samareh et al, 2009) that is focused on the simulation of the shock pattern in the jet using a two-way coupled Lagrangian approach. It was found that flow patterns could be predicted with high accuracy, including effects of high particle loading in the jet.…”
Section: Coupled Simulationmentioning
confidence: 99%
“…Fluent (version 6.3.26) commercial software was used in this work to predict the performance of the Cold Spray nozzles analyzed, combined with a study of particles trajectories and velocity within the jet flow. Samareh et al [17] have studied through a two-way coupling system the behaviour of particles in CS nozzles and effects on gas velocity for high particle loadings (60 to 180g/min), and by implementing advanced multiple equations turbulence models. Such models can be accurate, but are relatively difficult to consistently converge up to higher order schemes; also the loading of particles within the carrier gas in most Cold Spray applications is typically smaller, therefore within the range of sufficiently diluted flow (solid phase volume fraction <10%) [12,18]; particle-particle and particle-carrier gas interactions can be negligible.…”
Section: Cfd Simulation Of Cold Spray Nozzlesmentioning
confidence: 99%